DYNAMICS OF GROWTH AND INEQUALITY E-COMMERCE ADOPTION: A SECTORAL ANALYSIS OF DIGITAL ENTREPRENEURSHIP IN INDONESIA - Cut Dinda Sara; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty (RADJA PUBLIKA, 2025)
This study aims to analyze the disparity in e-commerce adoption by entrepreneurs across Indonesia. Using quantitative descriptive methods, this study processed secondary data sourced from the E-Commerce Statistics report from the Central Statistics Agency (BPS). The results show significant differences in the use of digital technology across regions. Java Island recorded the highest digital adoption rate, supported by established infrastructure. Conversely, eastern Indonesia, such as Papua, showed the lowest adoption rate due to internet access and logistical constraints. These findings emphasize the importance of equitable digital ecosystems to support the sustainability of entrepreneurship across Indonesia.